Mass-forming type 2 autoimmune pancreatitis with upstream dilatation of the main pancreatic duct dilatation: a case report - Noriyuki Tagai; Takanori Goi; Kenji Koneri; Makoto Murakami (Journal of Medical Case Reports)
Abstract Background Type 2 autoimmune pancreatitis is characterized by multiple or segmental strictures of the main pancreatic duct without upstream dilatation. We encountered a case of mass-forming type 2 autoimmune pancreatitis with upstream main pancreatic duct dilatation that was difficult to diagnose preoperatively using endoscopic ultrasound sonography-guided fine-needle aspiration cytology. Case presentation A 58-year-old Japanese man presented with recurrent acute pancreatitis secondary to a 10-mm pancreatic head tumor. The tumor compressed the main pancreatic duct, thereby dilating the upstream main pancreatic duct. The serum immunoglobin G4 levels were within normal limits. Endoscopic ultrasound sonography-guided fine-needle aspiration cytology was performed twice. However, few degenerative atypical cells were observed, resulting in an indeterminate diagnosis. The patient underwent pancreaticoduodenectomy, and pathological findings revealed duct-centric pancreatitis with neutrophilic infiltration of the interlobular pancreatic ductal epithelium. Immunoglobin G4-positive cells were not detected. The patient was diagnosed with type 2 autoimmune pancreatitis. Conclusion Mass-forming type 2 autoimmune pancreatitis can present with main pancreatic duct strictures and upstream dilatation. Although endoscopic ultrasound sonography-guided fine-needle aspiration cytology is useful for the diagnosis of solid pancreatic masses, preoperative diagnosis of type 2 autoimmune pancreatitis remains challenging. Further studies should be conducted to determine whether “hidden” type 2 autoimmune pancreatitis may be more frequently present and to improve the accuracy of the diagnosis of type 2 autoimmune pancreatitis.